The nature and fate of natural resins in the geosphere-II. Identification, classification and nomenclature of resinites - Anderson, K.B.; Winans, R.E.; Botto, R.E.
A classification scheme for resinites is proposed. Most resinites may be classified, on the basis of structural characteristics, into one of four classes. In order to exclude the effects of structural changes which reflect differences in the relative maturity of different samples, classifications are based on the structural character of the original resin from which the resinite was derived. In all samples characterized to date, this may be reasonably inferred from analytical data concerning the structure and composition of the individual sample. Class I resinites, which are by far the most abundant form of resinite in the geosphere, are derived from resins based primarily on polymers of labdatriene (diterpenoid)carboxylic acids, especially communic or ozic acids. Class II resinites are derived from resins based on polymers of sesquiterpenoid hydrocarbons, especially various isomers of cadinene. Class III resinites are natural polystyrenes. Class IV resinites are the least well characterized of the four resinite classes defined, but appear to be largely non-polymeric materials, dominated by sesquiterpenoids based on the cedrane carbon skeleton. Resinites belonging to Class I are further subdivided into three sub-classes on the basis of details of their composition. Class Ia resinites, which include succinite and related "Baltic ambers", are derived from resins based primarily on communic acid and incorporate significant amounts of succinic acid into their macromolecular structure. Class Ib resinites are also derived from resins based primarily on communic acid, but do not contain succinic acid. Class Ic resinites are derived from resins based primarily on labdatrienoic acids of the enantio series, especially ozic and/or zanzibaric acids. The structure, origin, and identification of resinites of each class are discussed. The effects of maturation on the structure of Class I resinites, and the consequences of these changes for the recognition and classification of this form of resinite are also briefly discussed.
Keywords: AMBER; CLASSIFICATION; MATURATION; NMR; PY-GC-MS; PYROLYSIS; RESINITE